2009
DOI: 10.1089/ten.tea.2008.0528
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Surface-Modified Contact Lens for the Transfer of Cultured Limbal Epithelial Cells to the Cornea for Ocular Surface Diseases

Abstract: Our aim was to develop an improved cell transfer system for delivering laboratory-cultured human limbal epithelial cells to the cornea, which would be low risk for the patient and convenient to use for the surgeon. We took a standard contact lens and developed a plasma polymer layer for coating this for attachment of cells to the lens and subsequent transfer of cells to the cornea. A range of plasma polymer surfaces were examined for initial cell attachment using three different combinations of human and rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 31 publications
1
49
0
4
Order By: Relevance
“…Deshpande et al have demonstrated that acid-functionalized surfaces deposited by plasma polymerization are able to support human and rabbit corneal epithelial cell proliferation in vitro. 30 The current study demonstrates the suitability of this technique for successful transfer of cultured corneal epithelial cells onto the wounded corneal surface and confirms that transferred labeled cells survive, proliferate, and undergo stratification in vivo.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…Deshpande et al have demonstrated that acid-functionalized surfaces deposited by plasma polymerization are able to support human and rabbit corneal epithelial cell proliferation in vitro. 30 The current study demonstrates the suitability of this technique for successful transfer of cultured corneal epithelial cells onto the wounded corneal surface and confirms that transferred labeled cells survive, proliferate, and undergo stratification in vivo.…”
Section: Introductionsupporting
confidence: 73%
“…30 However, Deshpande et al seeded suspended corneal epithelial cells that require 3T3 feeder cells, 30 which are less desirable for clinical use. Previous studies have demonstrated feeder-free explant culture of corneal epithelium on commercial siloxane-hydrogel lenses in vitro 25 and a pilot study on humans produced clinical improvement in three patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations